2021
DOI: 10.3389/fphar.2021.600618
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ in Ischemia-Reperfusion Injury: Overview of the Biology and Therapy

Abstract: Ischemia-reperfusion injury (IRI) is a complex pathophysiological process that is often characterized as a blood circulation disorder caused due to various factors (such as traumatic shock, surgery, organ transplantation, burn, and thrombus). Severe metabolic dysregulation and tissue structure destruction are observed upon restoration of blood flow to the ischemic tissue. Theoretically, IRI can occur in various tissues and organs, including the kidney, liver, myocardium, and brain, among others. The advances m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 166 publications
1
13
0
Order By: Relevance
“…Therefore, it is considered to be a promising therapeutic target for treating I/R injury. 49,50 In this study, we observed enhanced PPAR-γ expression and inhibited phosphorylated NF-κB p65 expression in LPS-treated macrophage cells, suggesting that the PPAR-γ/NF-κB signaling pathway is involved in the antiinflammatory mechanism of PBzyme. These results illustrate that PBzyme has an excellent antioxidative function, antiinflammatory effect, and outstanding potential in the treatment of I/R injured skin flaps.…”
Section: Resultssupporting
confidence: 49%
“…Therefore, it is considered to be a promising therapeutic target for treating I/R injury. 49,50 In this study, we observed enhanced PPAR-γ expression and inhibited phosphorylated NF-κB p65 expression in LPS-treated macrophage cells, suggesting that the PPAR-γ/NF-κB signaling pathway is involved in the antiinflammatory mechanism of PBzyme. These results illustrate that PBzyme has an excellent antioxidative function, antiinflammatory effect, and outstanding potential in the treatment of I/R injured skin flaps.…”
Section: Resultssupporting
confidence: 49%
“…Once activated by its agonists, downstream transcription and expression effects are regulated [ 13 ]. The activation of PPAR γ leads to the amelioration of renal, hepatic, cerebral, myocardial, and other tissues of IRI [ 14 ]. This indicates that PPAR γ is a potential therapeutic mediator in IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is a major player in the development of ischemic injury that is initiated by leukocytes infiltration and proinflammatory cytokines production following I/R. 2 In the current study, inflammation was measured both systemically and locally. I/R systemically increased serum CRP and locally increased renal TNF-α level.…”
Section: Discussionmentioning
confidence: 99%
“…2 The mechanisms of I/R-induced acute kidney injury involve hypoperfusion, inflammation, and reactive oxygen species (ROS) production. 2 Leukocytes are among major players that may fuel the inflammatory response. During early phase of reperfusion, there is a rapid increase in the levels of various pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%